Os protagonistas do Araguaia: trajetórias, representações e práticas de camponeses, militantes e militares na guerrilha (1972-1974) - Mechi, Patricia Sposito (2012)
The guerrilla occurred between 1972 and 1974 in the southern states of Para and Maranhão, and the northern state of Goiás (now Tocantins). It involved about 70 activists of the Communist Party of Brazil, which organized it, and some residents who have joined the movement. Both groups were repressed by the military, who acted in the region arresting, torturing and murdering peasants and guerrillas. This research aims to study the representations and practices of social groups who staged this event: peasants, militants PC do B and the military. The intention was to understand the way that each group walked to get to the Araguaia and the region, which were the goals that were intended to fulfill and the practices adopted to achieve them. The research has as sources the testimonies of the peasants of the region, the documentation produced by the Communist Party of Brazil on guerrilla warfare, and military records on transactions, are official records and reports and books written by some of the army officers involved in the repression